16 Days Campaign, Albania, Bulgaria, Croatia, Georgia, Moldova, Montenegro, Serbia, Slovakia, Ukraine
Eleven public service announcements on the tape. In order: 1. Slovakia (in Slovakian) 2. Croatia (in Croatian) 3. Georgia (in Georgian) 4. Bulgaria (in Bulgarian) 5. Moldova (in Romanian) 6. Serbia (in Serbian) 7. Serbia (in Serbian) 8. Ukraine (in Ukrainian) 9. Montenegro (in Serbian Ijekavian dialect), 10. Albania (in Albanian) 11. Ukraine (in Ukrainian); Country:Albania, Bulgaria, Croatia, Georgia, Moldova, Slovakia, Ukraine, Yugoslavia